Rancang Bangun Teaching Aid Data Communication Sebagai Perangkat Pembelajaran Praktikum Komunikasi Data IoT dan Mikrokontroler - Abadi, Sarosa Castrena; Budiyarto, Aris; Supriyanto, Hadi; Suhada, Muhammad Giri; Ramdani, Cepi (Majalah Ilmiah Teknologi Elektro; Vol 23 No 2 (2024): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2024.v23i02.P15, 2025)
Learning media serves as a supplementary instrument, devised with the objective of streamlining the pedagogical process. This pedagogical tool assists educators in conveying material in a more lucid and engaging manner, thereby facilitating student comprehension of the subject matter. The paucity of learning aids in the laboratory of the Department Teknik Otomasi Manufaktur dan Mekatronika, Politeknik Manufaktur Bandung, impedes the efficacy of the learning process, particularly in regard to practicum activities necessitating a comprehensive grasp of data communication, microcontrollers, and Internet of Things (IoT) technology. Accordingly, the objective of this research is to construct a teaching aid device comprising an assortment of Internet of Things (IoT)-based data communication modules and STM32 and ESP32 microcontrollers. The research methodology employs the 4D method, encompassing the phases of Define, Design, Development, and Dissemination. The functionality test results indicate that each module operates in accordance with the stipulated specifications. However, the usability test results yielded an average score of 55.3, indicating the necessity for further refinement to enhance the ease of use of the teaching aid device. The dissemination of the device is facilitated through socialization activities within the broader community and its incorporation into practicum lectures.